Isolasi dan Identifasi Mikroba Rumen Penghasil Antihistamin “Histamine Methyl Transferase“ - Ning Iriyanti; Budi Rustomo; Efka Aris Rimbawanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2009)
The aim of this research was to find antihistamine ”Histamine Methyl Transferase” of microbe producers through isolation and testing of their activities on various substrates. The isolation process found four putative isolates i.e. N2k, N2b, N3 and N5. Their general characteristics were round, big and formed regular colonies; regular edge and wavy colonies. Colonies were whitish, shiny and had low convex elevation. N2k, N2b, and N5 isolates were Gram negative bacteria whereas N3 was Gram positive. Those isolates were non-motile. Further tests were conducted to examine the isolate capability to produce catalase and utilize citric acid as the carbon source to which they showed positive result. Nitrate reduction test showed positive results for N2b and N5 but not forN2k and N3. The ability to ferment sugars into acid and gas indicated that all isolates except N3 were capable of fermenting glucose and lactose. However, only N2k was capable to produce gas.